Pricing and Investment Policies in a System of Competitive Commuter Railways - Kanemoto, Y. (Review of Economic Studies, 1984)
This paper develops a simple spatial equilibrium model of a city served by competing commuter railways and analyses the effects of different transportation policies on their pricing and investment decisions. It is shown that a system of competitive railway companies does not achieve the optimal allocation. We then examine whether or not three types of government intervention, i.e. subsidies to railway companies, a rate-of-return regulation, and the ownership of residential land by railway companies, can achieve the optimal allocation.